ACTUALIZATION OF LEGAL PHILOSOPHY IN THE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Rosalina Simanungkalit; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
This study aims to analyze the actualization of legal philosophy in the criminal justice system and review critical theory in efforts to deal with crime in society. Legal philosophy has an important role in shaping the basics of legal thinking and directing the development of an effective criminal justice system. Meanwhile, critical theory provides a critical view of the existing legal system and highlights social, economic, and political aspects that influence crime prevention. This research uses a descriptive-analytical research method by reviewing the relevant literature and literature. The analysis is carried out by studying the concepts of legal philosophy in the context of criminal justice, as well as analyzing critical theoretical reviews of the legal system and efforts to deal with crime in society. The results of the research show that the actualization of legal philosophy in the criminal justice system is important for ensuring justice and protecting individual rights. Principles such as the presumption of innocence, legal certainty and proportionality of punishment form the basis for carrying out the functions of criminal justice. In addition, a critical theory review highlights the importance of understanding the social, economic, and political factors that are at the root of crime problems. Crime prevention efforts need to involve a holistic approach that goes beyond mere criminal proceedings, involving rehabilitation programs, community empowerment, and increasing legal awareness.